Effect of sucrose and calcium pulsing on early season 'HAAS' avocado fruit exocarp colour change during ripening - Chuene, Dipuo Rebecca (My University, 2022)
Avocado fruit ‘Hass’ exocarp changes colour from green to purple and black during ripening. However, uniform purple or black exocarp colour is not achieved during ripening, leading to consumers' rejection of fruit for not meeting quality standards. Avocado ‘Hass’ fruit harvested early remain green or develop a multicoloured appearance, concurrently devaluing their commercial value; and, therefore, unattractive to consumers. Therefore, this study aimed to investigate the role of sucrose and calcium postharvest pulsing on early matured ‘Hass’ avocado exocarp colour change during ripening. In this study, early matured ‘Hass’ avocado fruit were harvested from Halls and Sons, Mataffin farm (25°25’39.13” S, 30°55’52.84” E), Nelspruit, South Africa with 10 cm pedicel at commercial dry matter content (22%). Thereafter, the fruit were transported to the University of Mpumalanga laboratory. In the laboratory, the study was divided into two experiments: Experiment 1 ‘Hass’ fruit were continuously infused through the pedicel with different sucrose concentrations; 0 (control), 0.2 and 0.5 mM L-1. Experiment 2 fruit were infused with different calcium chloride (CaCl2) concentrations; 0 (control), 2 and 3 mM L-1. In both experiments, treated and untreated fruit were stored at 5.5°C for 28 days. After removal from cold storage, fruit were ripened at room temperature (±25°C) and evaluated every other day for firmness, subjective colour (visual colour), objective colour parameters (lightness-L*, chroma-C* and hue angle- h°), external chilling injury and ripening percentage. The results showed that Su (0.2 mM L-1) pulsing extended the ripening period by one day, corresponding with maintained fruit firmness. Furthermore, Su (0.2 mM L-1) treated fruit reduced the ‘Hass’ avocado fruit chilling injury index (CII) during cold storage. With respect to colour change, Su (0.5 mM L-1) treated fruit developed purple colour when compared with Su (0.2 mM L-1), which only developed to olive colour on the final ripening day (day 6). In addition, the results showed that all sucrose concentrations had a significant decreasing effect (P < 0.05) on objective colour parameters (L*, C* and h°) and increasing visual colour rating. With respect to CaCl2 treatments, fruit firmness decline was significantly delayed, which resulted in extended ripening time. Moreover, CaCl2 (2 and 3 mM L-1) significantly decreased (P < 0.05) pericarp objective colour parameters (L*, C* and h°) and increased visual colour rating and developed purple colour on the final ripening day (days 6 and 8, respectively). In addition, pulsing with CaCl2 (2 and 3 mM L-1) concentration reduced chilling injury during storage compared with control fruit. In conclusion, the results of this study indicated that Su and CaCl2 applied as postharvest treatments may contribute to avocado colour development by increasing anthocyanin accumulation. However, future research is required to investigate whether these treatments affect anthocyanin biosynthesis at the gene level.
Thesis (M.Sc.( Agriculture (Horticulture)) -- University of Limpopo, 2022
Keywords: Calcium chloride; Chilling injury; Exocarp colour; Hass avocado; Sucrose; Sucrose; Calcium chloride; Avocado; Avocado industry; Harvesting; Postharvest diseases and injuries